'In-Format' screening of a novel bispecific antibody format reveals significant potency improvements relative to unformatted molecules. Issue 1 (2nd January 2017) - Scott, Martin J.; Lee, Jennifer A.; Wake, Matthew S.; Batt, Kelly V.; Wattam, Trevor A.; Hiles, Ian D.; Batuwangala, Thil D.; Ashman, Claire I.; Steward, Michael
ABSTRACT: Bispecific antibodies (BsAbs) are emerging as an important class of biopharmaceutical. The majority of BsAbs are created from conventional antibodies or fragments engineered into more complex configurations. A recurring challenge in their development, however, is the identification of components that are optimised for inclusion in the final format in order to deliver both efficacy and robust biophysical properties. Using a modular BsAb format, the mAb-dAb, we assessed whether an 'in-format' screening approach, designed to select format-compatible domain antibodies, could expedite lead discovery. Human nerve growth factor (NGF) was selected as an antigen to validate the approach; domain antibody (dAb) libraries were screened, panels of binders identified, and binding affinities and potencies compared for selected dAbs and corresponding mAb-dAbs. A number of dAbs that exhibited high potency (IC50 ) when assessed in-format were identified. In contrast, the corresponding dAb monomers had ∼1000-fold lower potency than the formatted dAbs; such dAb monomers would therefore have been omitted from further characterization. Subsequent stoichiometric analyses of mAb-dAbs bound to NGF, or an additional target antigen (vascular endothelial growth factor), suggested different target binding modes; this indicates that the observed potency improvements cannot be attributed simply to an avidity effect offered by the mAb-dAb format. We conclude that, for certain antigens, screening naïve selection outputs directly in-format enables the identification of a subset of format-compatible dAbs, and that this offers substantial benefits in terms of molecular properties and development time.